Violência por parceiro íntimo contra mulher: adoção de condutas favoráveis a detecção de violência pelo profissional no espaço do exame preventivo - Ramos, Rayza de Sousa (2024)
The main objective of this study was to verify to what extent health professionals working in Pap smears have adopted conduct capable of contributing to the detection and assistance of IPV against women, as well as what factors would be possibly associated with the adoption of such conduct by professionals. Therefore, a quantitative, descriptive, exploratory and cross-sectional study was proposed, carried out in the UBS located in the urban area of the city of Manaus/AM with women with an intimate partner for at least 12 months and who underwent the colpocytopathological examination. A sociodemographic questionnaire, use and abuse of alcohol and drugs, and the Revised Conflict Tactics Scale 2 (CTS-2) were used. In addition to the descriptive analysis of the data, an exploratory analysis was carried out using the chi-square test to verify possible associations between the adoption of professional behaviors favorable to the diagnosis and assistance of IPV with the other independent variables under study. Were adopted a confidence interval of 95% and a significance level of 5%. The west zone of Manaus, the professional adopted more frequently the conduct of investigating the intimate relationship of the woman and of investigating her habits and behaviors, however, obtained less frequency to carry out the examination of violence signs. UBS user women who were most frequently investigated in their habits and behaviors are between 30 and 39 years old and only 8 women were approached about the topic of violence by the professional. Professionals more frequently adopted the conduct of investigating the intimate relationship of women who had high school, and more frequently adopted the conduct of examining violence signs in women with university education. White women were less likely to investigate habits and behaviors, and professionals were more likely to investigate intimate relationships with women who had their own income. The intimate relationship investigation occurred more frequently in women who underwent the preventive examination within 6 months and the intimate relationship and habits and behaviors were also investigated when the professional introduced himself and explained the procedure. It is noted that the professional addressed the topic of violence with women who suffered severe psychological violence. It was observed that the majority of female UBS users suffered some type of violence, the most common being psychological violence. Among victims of IPV, most return to the UBS, and had their gynecological consultation within 20 minutes, with the vast majority not exceeding 10 minutes. It was noticed that professionals who perform Pap smear test take, on their own, behaviors that favor the detection of IPV, although they are not the majority. With training, knowledge of coping networks, IPV can be given visibility as a matter of health problems. The factors that come to collaborate for the adoption of the conducts are the longer consultation time along with presenting to the patient and explaining the procedure, therefore, it is suggested to add to the protocol of the pap smear favorable conducts to the detection of violence, since that female UBS users mostly experienced some type of violence